2021
DOI: 10.21203/rs.3.rs-580431/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive Analysis of Prognostic and Immune Infiltrates for CBX Family in Human Pancreatic Adenocarcinoma

Abstract: Background: Pancreatic adenocarcinoma (PAAD) is one of the common Malignant tumours of the digestive tract worldwide. Chromobox (CBX) family proteins are important components of epigenetic regulation complexes and play key roles in various biological processes. However, the expression level, biological function and immune infiltration of different E2Fs in PAAD and prognostic roles of various CBX family members in Pancreatic adenocarcinoma (PAAD) remain unclear.Methods: In this study, we used multiple bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This also indicates that the up-regulation of CBX7 expression can exert anti-cancer effects by inhibiting cell migration and invasion. In addition, Li et al [31] found that the high expression of CBX3 mRNA and the low expression of CBX8 are independent risk factors for the shorter survival of patients with pancreatic cancer. Then Zhu et al [32] found that CBX2 mRNA and protein expression in CRC cells were higher than normal colonic epithelial FHC cells and para-cancerous tissues by real-time fluorescent quantitative PCR and western blot detection (both P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…This also indicates that the up-regulation of CBX7 expression can exert anti-cancer effects by inhibiting cell migration and invasion. In addition, Li et al [31] found that the high expression of CBX3 mRNA and the low expression of CBX8 are independent risk factors for the shorter survival of patients with pancreatic cancer. Then Zhu et al [32] found that CBX2 mRNA and protein expression in CRC cells were higher than normal colonic epithelial FHC cells and para-cancerous tissues by real-time fluorescent quantitative PCR and western blot detection (both P < .05).…”
Section: Discussionmentioning
confidence: 99%